Spectrum of rapidly progressive (Crescentic) glomerulonephritis at a referral diagnostic center in Nepal: one year study (Journal of Pathology of Nepal, 2023)
Background: A clinical syndrome manifested by features of glomerular disease in the urinalysis and by progressive loss of kidney function over a comparatively short period is called rapidly progressive glomerulonephritis (RPGN). RPGN is also called Crescentic glomerulonephritis(CrGN). Crescentic glomerulonephritis (CrGN) is defined as active crescents involving >50% of the total glomeruli. We have done this study to find out the major cause of RPGN in Nepal.Materials and Methods: This is a one-year prospective study done in the department of renal pathology at Pratham Pathology Private Limited over one year (1st November 2021-30th October 2022). Data of all patients were evaluated for the histopathological diagnosis. All cases of RPGN were included in the study. Evaluation of serological and demographic data, along with the number of active crescents was done.Results: A total of 182 cases of kidney biopsies were received for evaluation during one year (1st November 2021-30th October 2022) at Pratham Pathology Laboratory Private Limited, Kathmandu, Nepal. Out of it 18 cases (9.89%) were those of Crescentic glomerulonephritis. The most common cause of Crescentic glomerulonephritis encountered was Lupus Nephritis (7/18 cases). All cases of lupus presented with Crescentic glomerulonephritis were at stage IV. % of glomeruli with crescents ranged from 50-81.25% with mean involved glomeruli 60.61%.Conclusions: A total of 9.89% of the renal biopsies were presented with CrGN. Lupus nephritis was the most common cause of CrGN in Nepal.